2010
DOI: 10.1051/0004-6361/201015164
|View full text |Cite
|
Sign up to set email alerts
|

Quasar feedback revealed by giant molecular outflows

Abstract: In the standard scenario for galaxy evolution young star-forming galaxies transform into red bulge-dominated spheroids, where star formation has been quenched. To explain this transformation, a strong negative feedback generated by accretion onto a central supermassive black hole is often invoked. The depletion of gas resulting from quasar-driven outflows should eventually stop star-formation across the host galaxy and lead the black hole to "suicide" by starvation. Direct observational evidence for a major qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
703
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 598 publications
(767 citation statements)
references
References 43 publications
60
703
3
1
Order By: Relevance
“…We can also estimate the mass outflow rate to be ∼400 M yr −1 , which lies within the observed range 10 M yr −1 Ṁ out 10 3 M yr −1 (e.g. Feruglio et al 2010;Schönell et al 2014). The outflowing gas soon slows and entrains more gas, eventually stalling ∼100 kpc from the BH by t = 9.245 Gyr, when the rerun simulation ends.…”
Section: E F I N I T I O N O F O U T F L Ow Ssupporting
confidence: 79%
See 1 more Smart Citation
“…We can also estimate the mass outflow rate to be ∼400 M yr −1 , which lies within the observed range 10 M yr −1 Ṁ out 10 3 M yr −1 (e.g. Feruglio et al 2010;Schönell et al 2014). The outflowing gas soon slows and entrains more gas, eventually stalling ∼100 kpc from the BH by t = 9.245 Gyr, when the rerun simulation ends.…”
Section: E F I N I T I O N O F O U T F L Ow Ssupporting
confidence: 79%
“…The presence of outflows in luminous quasars and AGN has been evidenced in broad absorption lines (Lynds 1967). The nearest quasar Mrk 231 shows a multiphase outflow containing ionized, neutral (Rupke & Veilleux 2013;Teng et al 2014), and molecular gas (Feruglio et al 2010;Cicone et al 2012), which may be explained by a bipolar outflow and an accretion disc. Winds are also seen in Seyfert galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The [N II] line is indicative of hot HII regions rather than the PDR and can be used to estimate the fraction of [C II] emission that comes from ionized gas, rather than from PDRs. In many cases, the [N II] line is partially resolved and relatively broad (see Figure 9) and a sinc-Gauss profile was used to model the line in many instances where FWHM of ∼300-400 km −1 were measured, Although broad, these widths are still significantly smaller than those in systems that unambiguously are shown to have massive outflows (e.g., Feruglio et al 2010;Cicone et al 2014) Water is the second most oxygenated molecule (following CO) in the warm interstellar medium of galaxies and has been detected by Herschel in observations of nearby ULIRGs (González-Alfonso et al 2010;Rangwala et al 2011;PereiraSantaella et al 2013). The HERUS ULIRGs are also found to be abundant in water lines, in particular the ortho-H 2 O lines, IRAS 23230-6926, IRAS 06206-6315), and where the water lines, although detected, are significantly weaker than the CO lines (IRAS 09022-3615, IRAS 10565+2448, NGC 6240).…”
Section: Fitted Spectramentioning
confidence: 99%
“…Only very recently spatially resolved optical, far infrared and mm spectroscopic studies convincingly showed evidences for the existence of such processes in the form of the predicted energetic outflows in ULIRGs with Seyfert nuclei in the local Universe (e.g. Feruglio et al 2010;Fischer et al 2010;Rupke & Veilleux 2011;Villar-Martín et al 2011;Rodríguez-Zaurín et al 2013;Zhang et al 2011;Westmoquette et al 2012;Rupke & Veilleux 2013;Harrison et al 2014;McElroy et al 2014; see also Elvis 2000 for a discussion on the ubiquitous presence of winds in the AGN structure).…”
Section: Introductionmentioning
confidence: 99%